2016
DOI: 10.1038/srep33762
|View full text |Cite
|
Sign up to set email alerts
|

Combined Diffusion Tensor Imaging and Arterial Spin Labeling as Markers of Early Parkinson’s disease

Abstract: This study aimed to identify a PD-specific MRI pattern using combined diffusion tensor imaging (DTI) and arterial spin labeling (ASL) to discriminate patients with early PD from healthy subjects and evaluate disease status. Twenty-one early and 22 mid-late PD patients, and 22 healthy, age/gender-matched controls underwent 3-T MRI with apparent diffusion coefficient (ADC), fractional anisotropy (FA), fiber number (FN) and cerebral blood flow (CBF) measurements. We found that compared with healthy subjects, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 54 publications
4
34
1
Order By: Relevance
“…The small sample size may potentially account for differ- This is in agreement with the parallel circuits linking the basal ganglia and cortex (Alexander, DeLong, & Strick, 1986). This parallel loop model of striatal organization is broadly supported by studies of striatal anatomical and functional connections, hypoperfusion and hypometabolism using ASL and PET (Fernandez-Seara et al, 2012;Lehericy et al, 2004;Pappata et al, 2011;Postuma & Dagher, 2006;Wang et al, 2017;Wei et al, 2016). In addition, we found prolonged connectivity (Borghammer et al, 2010;.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The small sample size may potentially account for differ- This is in agreement with the parallel circuits linking the basal ganglia and cortex (Alexander, DeLong, & Strick, 1986). This parallel loop model of striatal organization is broadly supported by studies of striatal anatomical and functional connections, hypoperfusion and hypometabolism using ASL and PET (Fernandez-Seara et al, 2012;Lehericy et al, 2004;Pappata et al, 2011;Postuma & Dagher, 2006;Wang et al, 2017;Wei et al, 2016). In addition, we found prolonged connectivity (Borghammer et al, 2010;.…”
Section: Discussionsupporting
confidence: 85%
“…Arterial spin labeling (ASL) is a magnetic resonance imaging (MRI) method for quantifying cerebral blood flow (CBF) and arterial transit time (ATT) by using magnetically labeled arterial blood water as an endogenous tracer. Because it is entirely noninvasive, and needs no radioactive tracer or other contrast agent (Detre, Leigh, Williams, & Koretsky, ), ASL has been increasingly used to investigate perfusion in healthy controls (HCs) and several neurological and psychiatric disorders (Hales, Kawadler, Aylett, Kirkham, & Clark, ; Lin et al, ; Lui et al, ), including PD (Al‐Bachari et al, ; Al‐Bachari, Vidyasagar, Emsley, & Parkes, ; Fernandez‐Seara et al, ; Lin et al, ; Melzer et al, ; Wei et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, arterial spin labeling imaging combined with diffusion tensor imaging has been shown as useful markers for early Parkinson's disease [29]. In our study, PD patients showed reduced CBF in ve brain regions, i.e., the right cerebelum_crus2, the left MFG, the left IFG_Tri, the left FG_Med_Orb, and the left CN, as detected by 3D-pCASL.…”
Section: Discussionsupporting
confidence: 60%
“…By using radioisotopic tracers, depletion of blood flow can be traced by reduced glucose consumption in a particular brain region [143,144]. Apart from SPECT, MRI tensors are constantly tuned to detect early neoplasms and altered blood flow detection with high-resolution quality [145,146].…”
Section: Nift Application Example Hypothetical Model For Linking Highmentioning
confidence: 99%